To study knowledge of young girls and perception of cervical cancer: Probable improvement - Patil, Neha; Gite, Pranali; sharma, Gayatri; Patil, Akshay; Pardeshi, Rahul; Abhijit Bhanage, Avani (International Journal of Nursing Research, 2023)
The cervix is the lowest portion of the uterus and has stop growing by puberty. The cells will continue to divide to replace those that die of injury or old age. Carcinoma of the uterine cervix is the most common cancer in South Indian women and occupies the top rank among cancers in women in most developing countries, constituting 34% of all women‟s cancers. The ultimate need of the study is to prevent advanced stage cervix cancer by detecting it at early stage through screening. Aim: To educate adolescent girls about prevention of cervical cancer by valuation, this will improve their knowledge and help to prevent to reduce mortality and morbidity due to cervical cancer. Methods: A quasi pretest and post test experimental study design was used in this study among 60 selected 12th science adolescent girls at M.V.P‟S Arts, commerce and science college, ozar, Nashik selected by convenient sampling technique using structured questionnaire and semi structured interview schedule. Results: Demographic variables shows 83% of the samples were in the age group of 16-18 years with majority of the students belong to Hindu religion (85%), Muslim (7%), Christian (3%) and any others (5%). Conclusion: In assessment of knowledge and findings of the study reveals on prevention of cervical cancer that the mean knowledge score of pre test is 7.84 and the post test knowledge score and the mean knowledge score obtained is 12.67.